Increasing the physical and combustion performance of Oriental beech by impregnating borates and coating liquid glass - Gunbekler,Yilmaz Anil (2021)
Abstract This study was designed to investigate physical properties such as color changes after weathering and water absorption (WA) levels, and combustion performance of borates-impregnated and LG-coated Oriental beech wood. Results showed that borates impregnated and LG-coated Oriental beech wood showed positive lightness stability after weathering. The best color stabilization was obtained with LG-coated Oriental beech. Except for the 1 h WA period, LG did not show a water repellent effect after the water absorption test. Borates impregnation before LG-coating caused to decrease in weight loss of Oriental beech after the combustion test. Moreover, the lowest weight losses were obtained in borate impregnated Oriental beech wood.